Identifying the optimum water flow and number of buckets in laboratory-scale Pelton turbine using Central Composite Design (CCD). (July 2020) - Permanasari, A A; Puspitasari, P; Sukarni, S; Wulandari, R
Abstract: Pelton turbines were a type of water turbines which, principally, turned the water kinetic energy into electrical energy. The working principle of Pelton turbines was to utilize water power to produce turbine power. This paper reported the optimization of design parameters for laboratory-scale Pelton turbine using the central composite design (CCD) as the response surface methodology (RSM). This research obtained the quadratic polynomial equations for the turbine power. The independent variables were water flow (0.11 m 3 /s; 0.13 m 3 /s; 0.15 m 3 /s) and number of buckets (13; 15; 17 pieces). The results, based on the RSM, showed that the most influential parameter on the turbine power was the number of buckets. The optimum turbine power was 24 kW on 0, 16 m 3 /s water flow and 18 buckets of RSM.